The correlation between safety mindset, safety performance and safety culture in organisations - Hugo E. Botha,; E.I Edoun,; Vinessa Naidoo, (Technium Social Sciences Journal, 2020)
Understanding the factors leading a Safety Culture of Zero Harm has been a recurring topic of discussion and research for many decades. Pivotal to understanding a Safety Culture is to understand what the people in the work environment think about safety and how they do safety. For so long focus has always been on the doing part, which is the behaviour related to safety. The missing element is to scrutinise the ‘thinking’ which are core to the belief systems of people. Safe behaviour or at-risk behaviour can only be changed when these core beliefs are addressed. This study is to investigate the Safety Mindset, which is key to the foundation of the beliefs and to understand the relation of this mindset to the doing of safe safety. The essence is, therefore focussed on understanding the relationship between Safety Mindset (beliefs) and Safety Performance (Behaviours). The research in this dissertation sought to establish the correlation between Safety Mindset and Safety Performance and to understand how this significant combination leads to a Safety Culture of Zero Harm